PENGARUH MODEL PEMBELAJARAN KUMON TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP NEGERI 19 MERANGIN - Rohmi Yati; Ade Susanti (Pendidikan Matematika | STKIP YM Bangko, 2019)
This research is motivated by the lack of student mastery of the ability to solve mathematical problems. Some indicators of solving mathematical problems have not been able to be mastered well by students. For this reason, researchers used the Kumon learning model with the aim of being able to solve mathematical problem solving for eighth grade students of Merangin Public Middle School 19, which would be better than those taught by conventional methods. This research uses a quantitative approach with an experimental method. The study was conducted on 105th grade students of junior high school totaling 105 people. Data collection techniques through tests of mathematical problemsolving abilities in the form of essay questions. Data analysis techniques using tʹ. From the analysis of the final test data in the experimental class obtained an average of 35.65, while the control class obtained an average of 30.32. Hypothesis test results obtained, t' = 2.8808 and ttable = 2.0336. Because tarithmetic > Ttable then Ho is rejected and Ha is accepted. The conclusion of this study is the ability of students to solve mathematical problem solving in class VIII of SMP Negeri 19 Merangin by using the Kumon learning model better than students' mathematical problemsolving abilities taught by conventional methods.